The influence of socio-demographic characteristics on respondents’ perceptions of healthcare service quality - Manulik, Stanisław; Karniej, Piotr; Rosińczuk, Joanna (Journal of Education, Health and Sport, 2018)
Introduction: Service quality is the customer’s subjective assessment that plays an increasingly important role as an element of competitive advantage in the health sector. Aim: The main purpose was to determine whether the selected socio-demographic characteristics had a considerable impact on patients' quality priorities and their perceptions of service quality; and whether patients of public and private healthcare centres differed regarding their quality priorities and perceptions of the service they received.Material and methods: The study included 412 patients who were referred to a public (n=211) or a private (n=201) centre. The SERVQUAL questionnaire was used as the primary assessment tool. Respondents were to answer 22 questions grouped into five different dimensions that assessed their perceptions of service quality. Results: Respondents' expectations exceeded perceptions of service quality offered by public and private healthcare centres. Private sector respondents had the highest quality expectations regarding hardware and infrastructure, whereas public sector respondents were primarily concerned with relationships with personnel. The impact of socio-demographic characteristics on respondents' expectations and perceptions of healthcare service quality was unclear. Conclusion: Socio-demographic characteristics do not have a clear impact on patients' expectations and perceptions of healthcare service quality and as such, should not be used in the process of quality management.